A mind–body intervention for stress reduction as an adjunct to an information session on stress management in university students. Issue 6 (7th May 2020) - Cozzolino, Mauro; Girelli, Laura; Vivo, Deborah R.; Limone, Pierpaolo; Celia, Giovanna
Abstract: Introduction: This study describes the implementation of a mind–body intervention to reduce the perceived level of stress in a nonclinical group of university students. We used a novel approach including a single session of a mind–body technique known as the brain wave modulation (BWM) as an adjunct to a single information session on stress management. Methods: Three hundred and six students participated in the study. A quasi‐experimental design was adopted: Students in the experimental group were exposed to an information session on stress management followed by a single session of the BWM, while the other students were exposed to the information session alone. Results: A 2 × 2 mixed factor analysis of variance demonstrated that the single session of the BWM was effective in reducing the perceived level of stress in the experimental group as compared to the control group. Conclusion: The BWM is a very easy‐to‐learn technique that presents certain advantages over traditional mind–body methods. Abstract : This study describes the implementation of a mind–body intervention to reduce the perceived level of stress in a nonclinical group of university students. We used a novel approach including a single session of a mind–body technique known as the brain wave modulation (BWM) as an adjunct to a single information session on stress management. Results indicate that the single session of the BWM was effective in reducing the perceived level of stress in the experimental group as compared to the control group.